Removal of allergenic protein in natural rubber latex using protease from Bacillus sp. - Nanti, Suttiporn; Wongputtisin, Pairote; Sakulsingharoj, Chotipa; Klongklaew, Augchararat; Chomsri, Niorn (Food and Applied Bioscience Journal, 2017)
Natural rubber latex (NRL) contains more than 200 kinds of protein. Among these, 13 proteins have been regarded as an allergen that causes allergenicity to the user; especially healthcare workers. Thus, enzymatic degradation of these proteins using Bacillus sp. protease was introduced in this study instead of using chemical and physical method to reduce the allergenicity rick of NRL products. This study was aimed to produce protease powder from Bacillus sp. and determine minimum protease activity for NRL allergenic protein degradation. For the practical procedure, Bacillus sp. was cultured in Nutrient broth at 37oC, on rotary shaker at 150 rpm for 24 h and subsequently centrifuged to remove cells. Crude protease was precipitated by ammonium sulfate (80% saturation) and dialyzed (12 kDa cut off). Powder protease was prepared by freeze drying and yellowish powder of protease form Bacillus sp. was subsequently obtained. The remaining protease activity was 120, 422.53Units/ g powder, while specific activity was169.7 8 unit/mg proteins. Different amount of protease (0-500 unit) were added to fresh NRL serum and then incubated at 45oC for 6 hr. The remaining of allergen Hev b1 (rubber elongation factor; REF) was analyzed using western blot technique. REF could not be detected in NRL serum when more than 300 units of protease were added. Consequently, protease from Bacillus sp. could degrade REF in NRL.